Dehydroepiandrosterone (DHEA) Feeding Protects Liver Steatosis in Obese Breast Cancer Rat Model - Reza Hakkak; Andrea Bell; Soheila Korourian (MDPI AG, 2017)
Obesity is a major health problem in the US and globally. Obesity is associated with the risk of cardiovascular disease, type 2 diabetes, cancers, hyperlipidemia, and liver steatosis development. Dehydroepiandrosterone (DHEA) is a dietary supplement used as an anti-obesity supplement. Previously, we reported that DHEA feeding protects 7,12-dimethylbenz(a)anthracene (DMBA)-induced mammary tumors. The objectives of this study were to investigate the effects of obesity and DHEA feeding on liver steatosis, body weight gain, and serum DHEA, DHEA sulfate (DHEA-S), insulin-like growth factor-1 (IGF-1), and insulin-like growth factor binding protein-3 (IGFBP-3) levels. Female Zucker rats were randomly assigned to either a control diet or a control diet with DHEA supplementation for 155 days. Livers were collected for histological examination. Serum was collected to measure DHEA, DHEA-S, IGF-1, and IGFBP-3. Our results show that DHEA-fed rats had significantly less liver steatosis (p < 0.001) than control-fed rats and gained less weight (p < 0.001). DHEA feeding caused significant decreases (p < 0.001) in the serum levels of IGF-1 and IGFBP-3 and significantly increased (p < 0.001) serum levels of DHEA and DHEA-S. Our results suggest that DHEA feeding can protect against liver steatosis by reducing body weight gain and modulating serum IGF-1 and IGFBP-3 levels in an obese breast cancer rat model.